Improving Employee Performance through a Competency Perspective, Non-Physical Work Environment, Job Satisfaction, and Work Motivation Using Fishbone Analysis at the Pati District Health Service - Ummi Nur Latifah; Sunarno; Mamik Indaryani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze employee performance problems at the Pati District Health Service; analyze the causes that arise and the consequences in each perspective, namely the competency perspective, non-physical work environment, job satisfaction, and employee work motivation; analyzing supporting factors and inhibiting factors for improving employee performance; develop strategies to improve employee performance. This type of research is a descriptive approach, collecting in-depth interviews with 15 informants. Analysis method using the Fishbone approach. The results of the research concluded that performance problems were job placements that did not match their competencies. The Competency Perspective is due to lack of training, limited access to knowledge and developments in the health sector.